Pemberdayaan Desa Wisata Samiran Boyolali (Dewi Sambi) berdasarkan Teori Analisis Talc (Tourism Area Life Cycle) - Risky Ayu Andriani; Joko Winarno; Agung Wibowo (AGRITEXTS: Journal of Agricultural Extension, 2021)
Research on the development conditions of the Samiran Boyolali (Dewi Sambi) tourism village based on the TALC (Tourism Area Life Cycle) analysis theory is a descriptive qualitative study. The research location was determined purposively in Samiran Village, with the consideration that the Samiran tourism village was the first tourism village formed in Selo District together with the Lencoh tourism village in 2002. The purpose of this study was to investigate the process of empowering Dewi Sambi and identify the development of Dewi Sambi based on theory TALC. The determination of the informants was carried out by purposive sampling for key informants, while the advanced informants used snowball techniques based on recommendations from key informants. The number of informants in this study were 7 people including community leaders, village heads, managers, and members of Dewi Sambi. The data analysis technique of this research used the interactive inductive analysis method. Meanwhile, the validity of research data uses triangulation of sources and informant reviews. The results showed that the process of empowering Dewi Sambi went through 3 stages, namely the stage of awareness, breathing and power. These three stages were passed with the result that most of the people of Samiran Village joined Dewi Sambi and negative behavior began to wear off. The results of research on the development conditions of Dewi Sambi based on TALC, show that this tourism village is in a consolidation phase. The main characteristics that appear are the implementation according to regulations, the number of tourists fluctuating but tends to increase according to tourist visit chart, and the role of the ministry or government to improve services to tourist guests.